Introducing Educational Application of Neurodevelopmental Treatment for Children with Cerebral Palsy - Sina Mostowfi; Hamid Dalvand; Mohammad-Reza Hadian RasananiHadian Rasanani; Abbas Sheikhtaheri; Kheirolah Rahsepar Fard (Journal of Modern Rehabilitation, 2023)
Dear Editor in Chief The educational approaches have significantly changed and facilitated the teaching and learning process through the advent of novel technologies [1]. In the last years, learning through smartphones along with web-based learning has become 2 main types of e-learning platforms, especially during the COVID-19 pandemic; however, smartphones are a more acceptable approach compared to web-based learning because of their availability and easy use. Accordingly, developing smartphone-based learning packages may promote the participation of students in learning procedures. Currently, there are 16 billion mobile phones worldwide, of which about 42% are smartphones [2].